Near‐infrared light scattering and water diffusion in newborn brains. Issue 9 (9th August 2022) - Iwata, Sachiko; Katayama, Reiji; Tsuda, Kennosuke; Lin, Yung‐Chieh; Kurata, Tsuyoshi; Kinoshita, Masahiro; Kawase, Koya; Kato, Takenori; Kato, Shin; Hisano, Tadashi; Oda, Motoki; Ohmae, Etsuko; et al.
Abstract: Objective: MRI provides useful information regarding brain maturation and injury in newborn infants. However, MRI studies are generally restricted during acute phase, resulting in uncertainty around upstream clinical events responsible for subtle cerebral injuries. Time‐resolved near‐infrared spectroscopy non‐invasively provides the reduced scattering coefficient ( μ s ′ ), which theoretically reflects tissue structural complexity. This study aimed to test whether μ s ′ values of the newborn head reflected MRI findings. Methods: Between June 2009 and January 2015, 77 hospitalised newborn infants (31.7 ± 3.8 weeks gestation) were assessed at 38.8 ± 1.3 weeks post‐conceptional age. Associations of μ s ′ values with MRI scores, mean diffusivity and fractional anisotropy were assessed. Results: Univariable analysis showed that μ s ′ values were associated with gestational week ( p = 0.035; regression coefficient [ B ], 0.065; 95% confidence interval [CI], 0.005–0.125), fractional anisotropy in the cortical grey matter ( p = 0.020; B, −5.994; 95%CI, −11.032 to −0.957), average diffusivity in the cortical grey matter ( p < 0.001; B, −4.728; 95%CI, −7.063 to −2.394) and subcortical white matter ( p = 0.001; B, −2.071; 95%CI, −3.311 to −0.832), subarachnoid space ( p < 0.001; B, −0.289; 95%CI, −0.376 to −0.201) and absence of brain abnormality ( p = 0.042; B, −0.422; 95%CI, −0.829 to −0.015). The multivariable model to explain μ s ′ values comprised average diffusivity in the subcortical white matter ( p < 0.001; B, −2.066; 95%CI, −3.200 to −0.932), subarachnoid space ( p < 0.001; B, −0.314; 95%CI, −0.412 to −0.216) and absence of brain abnormality ( p = 0.021; B, −0.400; 95%CI, −0.739 to −0.061). Interpretation: Light scattering was associated with brain structure indicated by MRI‐assessed brain abnormality and diffusion‐tensor‐imaging‐assessed water diffusivity. When serially assessed in a larger population, μ s ′ values might help identify covert clinical events responsible for subtle cerebral injury.